A novel all-nitrogen molecular crystal N16 as a promising high-energy-density material. Issue 24 (8th June 2022) - Zhao, Lei; Liu, Shijie; Chen, Yuanzheng; Yi, Wencai; Khodagholian, Darlar; Gu, Fenglong; Kelson, Eric; Zheng, Yonghao; Liu, Bingbing; Miao, Mao-sheng
Abstract : A new all-nitrogen molecular crystal N16 with aromatic units, high molecular symmetry, and efficient crystal packing is predicted as a promising high-energy-density material that can be obtained under high pressure. Abstract : All-nitrogen solids, if successfully synthesized, are ideal high-energy-density materials because they store a great amount of energy and produce only harmless N2 gas upon decomposition. Currently, the only method to obtain all-nitrogen solids is to apply high pressure to N2 crystals. However, products such as cg-N tend to decompose upon releasing the pressure. Compared to covalent solids, molecular crystals are more likely to remain stable during decompression because they can relax the strain by increasing the intermolecular distances. The challenge of such a route is to find a molecular crystal that can attain a favorable phase under elevated pressure. In this work, we show, by designing a novel N16 molecule (tripentazolylamine) and examining its crystal structures under a series of pressures, that the aromatic units and high molecular symmetry are the key factors to achieving an all-nitrogen molecular crystal. Density functional calculations and structural studies reveal that this new all-nitrogen molecular crystal exhibits a particularly slow enthalpy increase with pressure due to the highly efficient crystal packing of its highly symmetric molecules. Vibration mode calculations and molecular dynamics (MD) simulations show that N16 crystals are metastable at ambient pressure and could remain inactive up to 400 K. The initial reaction steps of the decomposition are calculated by following the pathway of the concerted excision of N2 from the N5 group as revealed by the MD simulations.